Moralitas dalam Novel 728 Hari Ibu Jembatanmu Menuju Surga Karya Djono W.Oesman - Eka Ayu Permata Sari; Ida Bagus Jelantik; I Ketut Nama (Udayana University, 2021)
Novel 728 Hari Ibu Jembatanmu Menuju Surga by Djono W.Oesman was chosen as research data for several reasons. First, because this novel is a best seller. Second, this novel tells the true story of a person. Third, this novel has many useful references to morality. The analysis of this resersch uses structural theory and moral value theory as formulated by Burhan Nurgiyantoro’s. Structural theory discusses the object of research in the intrinsic elements that build and literary work, among others, characterization, plot, and setting. Moral value theory is uused analyze the morality contained in the novel. The method used in this research is the library research method with reading, listening, and note taking techniques. Then, the data were analyzed using the analytical descriptive method. The results of this study consist of two parts. First, the structure of the novel 728 Hari:IJMS, the characters in the novel are the main character, Eva Meliana Santi, and additional characters, namely Sugiarti, Badarudin, Ryantori Ahmad, and Winantyo Adi Tamtomo (Nanan). The flow used consisnts of three stages, namely the initial stages, the middle stages, and the final stages. The setting of this novel is divided into three, namely place setting, time setting, and social setting. Second, the morality contained in the novel 728 Hari:IJMS and the moral of the main character in dealing with life’s problems.